To the question of theatricality or what begins in the story of Dostoyevsky’s Uncle’s dream? - Berzaite, Dagne (Literatūra, 2019)
The article discusses the issue of theatricality arising from the reception of Dostoevsky’s novel Uncle’s Dream. Until now, researchers have dwelled on the external scenic elements of the story and have not paid much attention to the nature of the monologues of the main heroine of the story, where the orientation to directing and acting is obvious. Moskaleva’s monologues are not only built “in a theatrical manner” and foreshow the emergence of a complex dialogical structure characteristic of Dostoevsky’s main novels, but at the same time they reveal features characteristic of the future hero – the ideologist of Dostoevsky. And the identification of the Shakespearean leitmotif of the story supports the idea of it as a work in which theatrical elements are intertwined with the prosaic, and at the same time, it reveals the most important topics that are typical in the writer’s further work.